Pengukuran Kinerja Sistem Informasi Akademik Menggunakan Kerangka Kerja Cobit 4.0 - Rohmanto, Ricky; Furqon, Muhamad (Jurnal Accounting Information System (AIMS), 2025)
Currently, performance measurement is very necessary for institutions that already use information technology, this is intended to assess the extent to which the level of effectiveness and efficiency of IT is to support the goals of the institution. STMIK Sumedang has conducted management and evaluation in the field of information, but in its evaluation it has not used a structured method and approach, so this is considered necessary to assess the suitability between the goals of the institution and the management that has been carried out. COBIT is one of the frameworks used to assess, measure and control the performance of institutions in managing IS / IT. COBIT can also be accepted and aligned by its users, because this framework is built from the goals, rules & policies of the institution. Then all processes are analyzed by looking at the alignment between the goals to be achieved with the procedures / policies implemented by the institution. In this study, the author uses the latest version of COBIT (Control Objective for Information and Related Technology), namely version 4.1, in the Planning organization domain. COBIT is created and standardized by IT Governance, an institution that creates an IT governance model. There are 3 management guidelines used by the Author, namely CSF (Critical Success Factors), KPI (Key Performance Indicators) and KGI (Key Goal Indicators). The results of the study conducted are to create a performance measurement of the Academic Information System (AIS) in the form of analysis, maturity level mapping and recommendations for STMIK Sumedang, which is expected to be a management model for other institutions.